Hubungan Pengetahuan Dengan Sikap Pada Calon Jemaah Haji dan Umrah Lansia Terhadap Pencegahan Dehidrasi - Firda Amalia; Pritha Maya Savitri; Diana Agustini; Melly Kristanti (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: Hajj and Umrah are Islamic pilgrimages performed in Saudi Arabia, often taking place during the summer season when temperatures may exceed 40°C. Such extreme conditions increase the risk of dehydration, especially among the elderly. Dehydration in older adults can lead to severe complications, even death. Preventive measures can be achieved through adequate knowledge and positive attitudes toward fluid intake.Methods: This was an observational analytic study with a cross-sectional design. Respondents were selected using purposive sampling, consisting of 50 elderly Hajj and Umrah pilgrims. The study was conducted from February to December 2023 at the NRA Hajj and Umrah Bureau, South Jakarta. Data were analyzed using the chi-square test to assess the relationship between knowledge and attitudes toward dehydration prevention.Results: The majority of respondents had good knowledge (62%) and moderate attitudes (56%), with most being female aged 60–65 years. Bivariate analysis showed a significant relationship between knowledge and attitudes of elderly Hajj and Umrah pilgrims toward dehydration prevention (p = 0.035).Conclusion: There is a significant relationship between knowledge and attitudes of elderly Hajj and Umrah pilgrims toward dehydration prevention.